The 4.5S RNA gene from Pseudomonas aeruginosa. - Toschka, H Y (1989)
The essential 4.5S RNA of Escherichia coli contains a structural motif, which is also present in RNAs from other organisms, i.e. Bacillus subtilis scRNA, Halobacterium halobium 7S RNA and eukaryotic 7SL RNAs. This suggests a common function in all organisms, which could be related to protein translocation, since 7SL RNA is essential for this process in eukaryotes. We have analysed the structure and expression of the 4.5S RNA gene from another gram-negative eubacterium, Pseudomonas aeruginosa. The single copy gene encodes a 113 nucleotides long RNA, which shares 75% sequence homology to the E. coli 4.5S RNA and also exhibits the completely conserved hairpin structure of the corresponding RNAs of B. subtilis and E. coli. Transcription initiates 24 nucleotides upstream from the mature 5' end and exceeds beyond the 4.5S RNA coding region. A distal open reading frame, similar to that described for E. coli, does not exist downstream from the P. aeruginosa 4.5S RNA gene.